Double Inversion Recovery MR Sequence for the Detection of Subacute Subarachnoid Hemorrhage - Hodel, J.; Aboukais, R.; Dutouquet, B.; Kalsoum, E.; Benadjaoud, M.A.; Chechin, D.; Zins, M.; Rahmouni, A.; Luciani, A.; Pruvo, J.-P.; Lejeune, J.-P.; Leclerc, X. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: The diagnosis of subacute subarachnoid hemorrhage is important because rebleeding may occur with subsequent life-threatening hemorrhage. Our aim was to determine the sensitivity of the 3D double inversion recovery sequence compared with CT, 2D and 3D FLAIR, 2D T2*, and 3D SWI sequences for the detection of subacute SAH. MATERIALS AND METHODS: This prospective study included 25 patients with a CT-proved acute SAH. Brain imaging was repeated between days 14 and 16 (mean, 14.75 days) after clinical onset and included MR imaging (2D and 3D FLAIR, 2D T2*, SWI, and 3D double inversion recovery) after CT (median delay, 3 hours; range, 2–5 hours). A control group of 20 healthy volunteers was used for comparison. MR images and CT scans were analyzed independently in a randomized order by 3 blinded readers. For each subject, the presence or absence of hemorrhage was assessed in 4 subarachnoid areas (basal cisterns, Sylvian fissures, interhemispheric fissure, and convexity) and in brain ventricles. The diagnosis of subacute SAH was defined by the presence of at least 1 subarachnoid area with hemorrhage. RESULTS: For the diagnosis of subacute SAH, the double inversion recovery sequence had a higher sensitivity compared with CT (P < .001), 2D FLAIR (P = .005), T2* (P = .02), SWI, and 3D FLAIR (P = .03) sequences. Hemorrhage was present for all patients in the interhemispheric fissure on double inversion recovery images, while no signal abnormality was noted in healthy volunteers. Interobserver agreement was excellent with double inversion recovery. CONCLUSIONS: Our study showed that the double inversion recovery sequence has a higher sensitivity for the detection of subacute SAH than CT, 2D or 3D FLAIR, 2D T2*, and SWI. IVHintraventricular hemorrhageDIRdouble inversion recovery